Working Memory Capacity, Mind Wandering, and Creative Cognition: An Individual-Differences Investigation into the Benefits of Controlled Versus Spontaneous Thought - Smeekens, Bridget A. (Psychol Aesthet Creat Arts, 2016)
Should executive control, as indicated by working memory capacity (WMC) and mind-wandering propensity, help or hinder creativity? Sustained and focused attention should help guide a selective search of solution-relevant information in memory and help inhibit uncreative, yet accessible, ideas. However, unfocused attention and daydreaming should allow mental access to more loosely relevant concepts, remotely linked to commonplace solutions. Three individual-differences studies inserted incubation periods into one or two divergent thinking tasks and tested whether WMC (assessed by complex span tasks) and incubation-period mind wandering (assessed as probed reports of task-unrelated thought [TUT]) predicted post-incubation performance. Retrospective self-reports of Openness (Experiment 2) and mind-wandering and daydreaming propensity (Experiment 3) complemented our thought-probe assessments of TUT. WMC did not correlate with creativity in divergent thinking, whereas only the questionnaire measure of daydreaming, but not probed thought reports, weakly predicted creativity; the fact that in-the-moment TUTs did not correlate divergent creativity is especially problematic for claims that mind-wandering processes contribute to creative cognition. Moreover, the fact that WMC tends to strongly predict analytical problem solving and reasoning, but may not correlate with divergent thinking, provides a useful boundary condition for defining WMC’s nomological net. On balance, our data provide no support for either benefits or costs of executive control for at least one component of creativity.